Roles of Proton-Sensing Receptors in the Transition from Acute to Chronic Pain. (February 2016) - Sun, W.H.; Chen, C.C.
Chronic pain, when not effectively treated, is a leading health and socioeconomic problem and has a harmful effect on all aspects of health-related quality of life. Therefore, understanding the molecular mechanism of how pain transitions from the acute to chronic phase is essential for developing effective novel analgesics. Accumulated evidence has shown that the transition from acute to chronic pain is determined by a cellular signaling switch called hyperalgesic priming, which occurs in primary nociceptive afferents. The hyperalgesic priming is triggered by inflammatory mediators and is involved in a signal switch from protein kinase A (PKA) to protein kinase Cε (PKCε) located in both isolectin B4 (IB4 )–positive (nonpeptidergic) and IB4 -negative (peptidergic) nociceptors. Acidosis may be the decisive factor regulating the PKA-to-PKCε signal switch in a proton-sensing G-protein-coupled receptor-dependent manner. Protons can also induce the hyperalgesic priming in IB4 -negative muscle nociceptors in a PKCε-independent manner. Acid-sensing ion channel 3 (ASIC3) and transient receptor potential/vanilloid receptor subtype 1 (TRPV1) are 2 major acid sensors involved in the proton-induced hyperalgesic priming. The proton-induced hyperalgesic priming in muscle afferents can be prevented by a substance P–mediated signaling pathway. In this review, we summarize the factors that modulate hyperalgesic priming in both IB4 -positive and IB4 -negative nociceptors and discuss the role of acid signaling in inflammatory and noninflammatory pain as well as orofacial muscle pain.